Identification of mannose 6-phosphate in glycoproteins that inhibit the assimilation of β-galactosidase by fibroblasts - Distler, Jack (1979)
Bovine testicular β-galactosidase (β-D-galactoside galactohydrolase, EC 3.2.1.23) is rapidly and selectively assimilated by human skin fibroblasts. The assimilation of the enzyme is strongly inhibited by mannose 6-phosphate and by a glycoprotein fraction isolated from bovine testes (glycoprotein inhibitors). These results suggest that β-galactosidase and the glycoprotein inhibitors have a common recognition marker that contains mannose 6-phosphate. The presence of mannose phosphate in the glycoprotein inhibitors was demonstrated by acid hydrolysis of the glycoproteins to liberate mannose phosphate followed by reduction with NaB(3)H(4) to give [(3)H]mannitol phosphate. The (3)H-labeled compound was identified by paper electrophoresis and by the release of [(3)H]mannitol on treatment with phosphatase. The [(3)H]mannitol phosphate was oxidized with periodate and the resulting phosphorylated fragment, on reduction with NaB(3)H(4), yielded [(3)H]ethylene glycol phosphate, indicating substitution of phosphate on carbon 6 of mannitol. Mannose 6-phosphate was also found in a major carbohydrate-containing fraction of peptides produced from the glycoprotein inhibitors by tryspin digestion. It was estimated that about 2% of the mannose residues were present as mannose 6-phosphate. Phosphorylated oligosaccharides were also identified in hydrolysates of the glycoprotein inhibitors. One, a disaccharide, was identified as α-(mannosyl-6-phosphate)-(1 → 2)-mannose. These observations suggest that the recognition marker of β-galactosidase contains α1,2-linked mannose 6-phosphate; terminal α1,2-linked mannose residues are known to occur in the high-mannose type oligosaccharides present on β-galactosidase.